Simulation of the joint operation of an electric motor and a hydraulic coupling in a belt conveyor drive - Goncharov Kirill; Lagerev Alexander (Serbian Journal of Electrical Engineering, 2023)
The task of ensuring smooth movement of the conveyor belt during the operation of powerful belt conveyors with a long route and several intermediate electric drives is an urgent technical problem. One of the effective ways to solve this problem is to create drives that ensure the joint operation of an electric motor and a hydraulic coupling. In this article, a mathematical model of the joint operation of an electric motor and a hydraulic coupling is proposed. When constructing the mechanical characteristics of their joint work, possible deviations of the electric motor slip from the nominal values are taken into account. To simulate various possible approximating functions that describe the mechanical characteristics of the drive, two of the most accurate mathematical expressions that are used are the Kloss equation and the equation for interpolating hyperbolic functions. With regard to the electric drive of a powerful belt conveyor, the analysis of the appropriate areas of application of these dependencies is carried out, their main advantages and disadvantages are considered.